Call the midwife. Season one [videorecording (DVD)] - Payne, Jamie; Lowthorpe, Philippa; Worth, Jennifer, 1935-2011; Redgrave, Vanessa, 1937-; Ferris, Pam; Raine, Jessica, 1982-; George, Helen, 1984-; Agutter, Jenny; Parfitt, Judy, 1935- (Warner Home Video, 2012)
A moving, intimate, funny, and true-to-life look at the colorful stories of midwifery and families in East London in the '50s. Based on the bestselling memoirs of the late Jennifer Worth. When Jenny Lee first arrives in Poplar, she knows nothing about hardship, poverty, and life itself. But Jenny is brought up to speed fast once she joins a team of midwives who provide care to the poorest women.